Abnormal forms in Pinnularia gibba (Bacillariophyceae) in a polluted lowland stream from Argentina - Gomez, Nora (2003)
A study of samples collected in the Don Carlos Stream, a small stream that runs across an urbanised and industrialised area of the Pampean plain, displayed abnormalities in the valves of Pinnularia gibba Ehrenberg. Three stations were sampled in different sectors of the stream: station A was located upstream and exposed to agricultural activity, stations B and C were exposed to sewage effluent and to outflows from textile and metallurgical factories, respectively.Acetate sheets placed on bricks, fastened with several staples, were used as artificial substrata and exposed to colonisation during 21 days prior to collection. Diatoms from the artificial substrata were sampled during three weeks. Environmental variables analysed were pH, conductivity, dissolved oxygen, biological oxygen demand, chemical oxygen demand, hardness, total suspended solids and nutrients. Also heavy metals (Cu, Cr, Cd, Zn) were analysed in water and sediment. Two types of abnormalities were found in P.gibba: type I had valves exhibiting abnormal stration patterns and/or deformed or interrupted raphe and type II had deformities in the outline of the valves, sometimes linked to anomalies in the striae or raphe. Multiple correlation analysis showed a close relationship between the appearance of the deformations and water quality in the Don Carlos Stream.